Transformation of Toraja Ma'kombongan Culture to a Cooperative Learning Model - Roberto Salu Situru'; Dian Intan Tangkeallo; Josua Borean; Rannu Palebangan; Welly Slamet (Edumaspul: Jurnal Pendidikan, 2022)
The aim of this study is to identify and deepen the Ma'kombongan culture in the Toraja community as a collaborative learning model. In addition, the appointment of Ma'kombongan will preserve Torajan cultural values ​​in modern times. This study uses a qualitative research approach with data collection techniques through literature reviews and interviews with experts, traditional elders, and businesses of the Torajan community. The data was collected and the data coded. The research was conducted in three phases, the first phase was to collect studies in the form of books and to identify community leaders who were knowledgeable on the subject. The second stage is to conduct a literature review and interviews with community leaders. The third stage is to analyze the collected data to formulate a clear argument regarding the identification of Ma'kombongan as a learning model for group investigations. Ma'kombongan culture as a group collaborative learning model .